Pemanfaatan Barang Bekas sebagai Edukasi Pemilahan Sampah Rumah Tangga di Desa Lambuluo, Konawe Utara - Listy Handayani; Paridah Paridah; Ruwiah Ruwiah; Irma Irma; Ahmad Syahrul Umar; Fahrezi Ramadhan (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Household waste management in rural areas remains challenging due to limited sorting habits, inadequate facilities, and practices of burning or disposing waste into the environment. This community service activity aimed to provide an educational medium for organic and non-organic waste sorting by reusing discarded materials in Lambuluo Village, Motui District, North Konawe Regency. The activity used a simple participatory action approach based on environmental problem-solving and was conducted on 28–31 July 2025 by students of the Faculty of Public Health, Halu Oleo University. The intervention involved constructing two prototype waste bins from wooden frames and used paint buckets, labeling them for organic and non-organic waste, installing them in Hamlet 1 and Hamlet 3, and providing brief education and usage simulations for residents. Evaluation was carried out through field observation on 12 August 2025 using utilization, maintenance, and cleanliness indicators. The results showed that both waste bins remained in place, were used by residents, maintained, and kept clean, with all indicators achieving 100%. This activity demonstrates that simple facilities made from used materials can serve as practical, low-cost, and replicable educational media to promote household waste sorting, encourage reuse practices, reduce plastic waste, and support sustainable environmental management in village communities.